Perkembangan Sosial, Moral dan Spiritual Siswa Kelas V SDS Pahlawan Nasional - Fadillah, Nurul; Lubis, Ramadan; Azahra, Bella; Daulay, Fitri Ana; Brutu, Sabilla Meliani; Rahmadi, Ihsan (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to analyze the social, moral, and spiritual development of fifth-grade elementary school students through a case study of a student named Nindy. Using qualitative descriptive methods, data were collected through observation, interviews, and documentation to understand behavior and developmental processes in depth. The results of the study indicate that Nindy's social development is in the good category, characterized by the ability to work together, positive interactions, and adaptation in groups, in accordance with the Industry vs. Inferiority stage according to Erikson. In the moral aspect, Nindy shows compliance with rules, but her moral reasoning is still simple and is at the pre-conventional to early conventional stage according to Kohlberg's theory. Her spiritual development is manifested in the consistency of participating in religious activities, although the understanding of the meaning of worship is still in the imitation stage as explained by Hurlock. Overall, these three developmental aspects show conformity with the developmental tasks of elementary school children.